Measuring the Sciences Contribution to Socioeconomic Development: Russian Approaches in the Global Space of Ideas - A. A. Yanik (Модернизация, инновация, развитие, 2021)
Purpose: this review aims to present the ‘state-of-the-art’ on the theory and practice of measuring the contribution of sciences to socioeconomic progress and trace the Russian approaches in the global space of ideas.Methods: for studying a multidisciplinary sample of academic publications and gray literature includes multifactor systematization, critical analysis, and synthetic generalization in a large context («helicopter view»).Results: a brief history of the subject is presented in the context of the state's use of science for socio-economic development. The review outlines the focus areas of scientific thought, the conceptual frameworks state, current approaches to measuring the contribution of sciences, the limitations and risks of the evaluation practice.Conclusions and Relevance: key areas of scientific thought in the subject under review for 100 years: (1) development of econometric approaches for measuring the «profitability» of science; (2) attempts to identify and measure the societal impacts of science; (3) scientific support of government experiments to use the evaluation technologies for increasing the return of budget investment to science; (4) conceptualizing and universalizing the terms. There are no indisputable solutions in any of these areas. Disappointment with the catch-all indicators and universal metrics encourages the development of case-oriented methods and process-oriented approaches.Russian research covers the full range of issues, but their world recognition (except some achievements of Soviet time) is low. The lack of institutional memory leads to the rediscovery of the ideas of the 20th century. Establishing the equivalence of terms and conceptual approaches used by scientists from different countries and periods will help to effectively use the scientific heritage, avoid duplicate research, provide a fair place to the Russian achievements in world science.